Industrial ventilation design guidebook - Goodfellow, Howard D.; Tahti, Esko. (San Diego, Calif. ; London : Academic, 2001)
The Industrial Ventilation Design Guidebook addresses the design of air technology systems for the control of contaminants in industrial workplaces such as factories and manufacturing plants. It covers the basic theories and science behind the technical solutions for industrial air technology and includes publication of new fundamental research and design equations contributed by more than 40 engineers and scientists from over 18 countries. Readers are presented with scientific research and data for improving the indoor air quality in the workplace and reducing emissions to the outside environment. The Guidebook represents, for the first time, a single source of all current scientific information available on the subject of industrial ventilation and the more general area of industrial air technology. New Russian data is included that fills several gaps in the scientific literature. * Presents technology for energy optimization and environmental benefits * A collaborated effort from more than 60 ventilation experts throughout 18 countries * Based on more than 50 million dollars of research and development focused on industrial ventilation * Includes significant scientific contributions from leading ventilation experts in Russia * Presents new innovations including a rigorous design methodology and target levels * Contains extensive sections on design with modeling techniques * Content is well organized and easily adaptable to computer applications.
Industrial Air Technology -- Description -- Terminology -- Design Methodology of Industrial Air Technology (DM) -- Physical Fundamentals -- Physiological and Toxicological Considerations -- Target Levels -- Principles of Air and Contaminant Movement Inside and Around Buildings -- Room Air Conditioning -- Air Handling Unit and Ductwork -- Local Ventilation -- Design with Modeling Techniques -- Experimental Techniques -- Gas Cleaning Technology -- Pneumatic Conveying -- Environmental Assessment Tools -- Economic Aspects -- Appendix 1: Basic SI Units. Unit Conversion Tables. Symbols and Greek Alphabet. Physical Constants. Dimensionless Numbers. Definitions. -- Appendix 2: National Bodies.
Includes bibliographical references and index.
Keywords: Industrial buildings -- Heating and ventilation -- Design and construction; Ventilation -- Design and construction; Electronic books